2020
DOI: 10.3390/jcm9040965
|View full text |Cite
|
Sign up to set email alerts
|

People with Suspected COVID-19 Symptoms Were More Likely Depressed and Had Lower Health-Related Quality of Life: The Potential Benefit of Health Literacy

Abstract: The coronavirus disease 2019 (COVID-19) epidemic affects people’s health and health-related quality of life (HRQoL), especially in those who have suspected COVID-19 symptoms (S-COVID-19-S). We examined the effect of modifications of health literacy (HL) on depression and HRQoL. A cross-sectional study was conducted from 14 February to 2 March 2020. 3947 participants were recruited from outpatient departments of nine hospitals and health centers across Vietnam. The interviews were conducted using printed questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
534
10
37

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 503 publications
(633 citation statements)
references
References 66 publications
52
534
10
37
Order By: Relevance
“…While, depression symptoms in infected COVID-19 likelihood was not statically significant comparing to the no infected and infected groups. Nguyen HC et al found that the people with Suspected COVID-19 symptoms had a higher depression likelihood than those without COVID-19 (34).…”
Section: -Anxiety and Depression Symptoms In Infected Covid-19 Peoplementioning
confidence: 99%
“…While, depression symptoms in infected COVID-19 likelihood was not statically significant comparing to the no infected and infected groups. Nguyen HC et al found that the people with Suspected COVID-19 symptoms had a higher depression likelihood than those without COVID-19 (34).…”
Section: -Anxiety and Depression Symptoms In Infected Covid-19 Peoplementioning
confidence: 99%
“…Besides the consequences that this pandemic is having on public health (Onder, Rezza & Brusaferro, 2020), it stands to have an important impact on mental health (Fiorillo & Gorwood, 2020; Li, Wang, Xue, Zhao, & Zhu, 2020; Torales et al, 2020), including the mental state of patients who are suffering from the infection, family members who have lost loved ones due to this disease, health professionals, the general population and patients who had a mental health problem before the pandemic, who have seen their symptoms increase and/or have had their treatment disrupted (Duan & Zhu, 2020; Kang et al, 2020; Xiang et al, 2020; Wang et al, ). Several studies in Asia are reporting a higher prevalence of post‐traumatic stress disorders (PTSD) after COVID‐19 within the general population (Liu et al, 2020; Wang, Pan et al, 2020) and problems with anxiety and depression (Nguyen et al, 2020; Qiu et al, ; Cao et al, ; Wang, Di, Ye & Wei, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Social distancing, isolation, insecurity of food and survival, diminishing of personal interactions, public closure, aggravated and increasing clusters of virus outbreaks leading to the collapse of the health care system, loss of jobs with sudden unemployment, financial crisis resulted in confusion, which may have an impact on health and quality of life. Panic, mental health problems and depression emerged like previously reported in MERS-CoV [37]. Health literacy in the population is a tool to measure the reaction of the public and the related health outcomes in the management of the crisis [37].…”
Section: Symptomsmentioning
confidence: 57%
“…Panic, mental health problems and depression emerged like previously reported in MERS-CoV [37]. Health literacy in the population is a tool to measure the reaction of the public and the related health outcomes in the management of the crisis [37]. Lack of preparedness to the sudden onset of COVID-19 by governments, health care systems and organizations, as well as deficiency in diagnostic mechanisms, treatment options and management protocols further increased public insecurity globally.…”
Section: Symptomsmentioning
confidence: 84%